Entrepreneurship Revolution, Skill Acquisition, and Entrepreneurial Intention of Undergraduate Students of the Colleges of Education in North Central Nigeria - Adebisi, Kudirat Ibrahim (NIU Journal of Social Sciences, 2018)
The study investigated the relationship between entrepreneurial revolution and entrepreneurial intention; and the relationship between skills acquisition and entrepreneurial intention of undergraduate students of the Colleges of Education in North Central Nigeria. The study used cross-sectional survey design. A sample size of 362 respondents was computed using Solven’s formula. Data was collected using questionnaires as the main research instrument. Data analysis was done using Pearson correlation coefficient and regression analysis. The study found positive and significant relationship between entrepreneurial revolution and entrepreneurial intention; and positive and significant relationship between skills acquisition and entrepreneurial intention. The study concluded that undergraduate students need entrepreneurship skills for them to be able to engage in entrepreneurial activities. The study recommended the need to build an efficient entrepreneurial culture that is essential in the motivation of young graduates to have entrepreneurial intentions. Keywords: Entrepreneurship Revolution, Entrepreneurial Skills Acquisition, Entrepreneurial Intention, Undergraduate Students, Colleges of Education, North Central Nigeria.